Strengthening Parents and Alternative Care in Shaping Empathy and Preventing Bullying among Adolescents in Boarding School - Bona Intan Rahmaniah; Alfiasari; Sri Sulastri (SEAMEO CECCEP, 2021)
This study analyzed the influence of parenting and schools’ non-physical environment on empathy and bullying behavior among adolescents in boarding schools. The study was conducted at the Nurul Fikri Boarding School and Cendekia Baznas Boarding School, Bogor Regency, involving adolescents aged 12-15. The study population was the eighth and ninth-grade students of the Nurul Fikri Boarding School and Cendekia Baznas Boarding School. A total of 134 male and female adolescents participated in this study. Primary data collection was carried out using an online self-administered questionnaire whereas secondary data were collected from the boarding school. Primary data consisted of adolescent characteristics, parental characteristics, foster teacher characteristics, parenting styles of the father, mother, and foster teacher, non-physical environment of the boarding school, empathy skills, and bullying behavior (as offenders and victims). Female adolescents had better empathy skills and a lower tendency of bullying (as offenders and victims) than male adolescents. The PLS-SEM test showed that the mother’s parenting style had a significant negative effect on adolescent bullying behavior as offenders. Cognitive empathy was also found to have a direct influence on adolescent bullying behavior as offenders. Recommendations for related parties based on the results are also discussed.